The kinetics of a wheelchair sprinter racing the 100m final at the 2016 paralympic games - Barbosa, T. M.; Coelho, E. (ISBS Proceedings Archive (Michigan), 2017)
The aim was to run a case study of a wheelchair sprinter`s kinetics racing the 100m final at the 2016 Paralympic Games. The model features data collected beforehand by experimental testing, data collected over the race and a set of assumptions. Speed was measured by video analysis. Energy output and energy input (being the sum of the energy of the rolling friction, energy of the drag and kinetic energy) were estimated employing an analytical model. Energy input and output increased over the event. The Einput and Eoutput in the first split represents 27.66% and 17.18% of what was delivered in the end of the race. However we failed to note a steady-state or an impairment of both parameters in the last meters of the race. Data suggests that the 100m is a very short event, being the sprinter unable to achieve his maximal power in such distance.